An integrated carbon and sustainability index from green buildings in the tropics - Jahn Kassim, Puteri Shireen; Hashim, Khairusy Syakirin Has-Yun; Hussien, Mohamad Zainuddin; Riduan, Basyirah (The Chartered Institution of Building Services Engineers (CIBSE), 2015)
Recently, there has been an increasing interest on bridging simulation and performance due rising concerns on the observed discrepancy or gap between green building targeted performance and the actual performance of buildings-in-use, especially in terms of energy performance in buildings. As energy is the primary component of carbon emission from buildings in the tropics due to dominant air conditioning loads, an integrated rating system of both carbon and sustainability assessment for tropical buildings which focuses its scoring weightage on energy reductions is proposed. The system will be implemented firstly in government buildings and then later to be launched for commercial buildings. The aim of this paper is to highlight the main principles, methods and process of assessment, certification and awards, system based on the proposed rating system. The fundamentals of the rating system is presented including how the system creates incentives to encourage future and existing building owners lower carbon emissions, and how the system integrates carbon impact assessment through calculators and the efforts in attempts to bridge, design, performance and operations and introduce life cycle concepts in operational and embodied carbon into a more holistic rating system for green buildings in the tropics.